ANALISIS PENGARUH JARAK DAN WAKTU TERHADAP PENURUNAN TEMPERATUR ASPAL PANAS (ASPHALT HOTMIX) PADA PROYEK JALAN BOLA HALE, KABUPATEN SIKKA NTT - Richardus Nurak; Yono Putra; Dedi Imanuel Pau (SIARTEK - Jurnal Teknik Sipil dan Arsitektur, 2024)
Asphalt is a road-supporting component that is commonly found on every road. In pratice, the temperature of the hotmix asphalt is critical to pay attention to when spreading. Therefore, asphalt will melt if heated to a certain temperature and then freeze again at lower one. Distance and temperature are always inversely related; the separation between the Asphalt Mixing Plant (AMP) and the place of the spreading is what determines how much the temperature drops. This research aimed to determine the effect of distance and time on reducing the temperature of hotmixasphalt. The research method used the experimental method (direct measurement). Temperature measurements were taken when the asphalt had just been poured into the truck and when the asphalt arrived at the spreading location. The research result of the temperature reduction on hotmix asphalt at the Route 1 laying location were 130 c over a distance of 66 km and the results of temperature reduction on Route 2 were 100 c over a distance of 26 km. This density test aimed to determine and take samples of pavement in the field so that the thickness and characteristics of the pavement mixture can be identified. The density result for test object one was 98.46%, test object two was 100.26%, and object test three was 98.06% density.